Influence of an intervention plan and early stimulation in the improvement of motor performance in early education T1, in preschool belonging to a private school in Temuco, Chile. (Revista horizonte, 2013)
The purpose of the study was to determine if there are significant changes in the motor behaviors of children after the application of an early stimulation program aimed at transition level I (4-5 years) of kindergarten education. METHODS: the study is framed in an action-research paradigm with a sample of 24 preschool subjects of both sexes, 14 females (58 %) and 10 males (42 %) from a private school in Temuco, chosen intentionally (GE n=24). The first evaluation of motor behaviors was performed before starting the early stimulation program and the second evaluation was performed at the end of the program through the quantification of motor skills: jumping feet together (SPJ), deep jumping (SP), throwing (LANZ), reception (REC), Flemish static balance (EQ. EST), total score of motor tests and average per test. Results: with an early stimulation program of 4 months duration with 1 weekly session, we found a significant increase (p0.05). Conclusions: early stimulation programmed during the physical education session induces significant improvements in the variables SPJ, LANZ, EQ. EST, total score of motor tests and average score per test in subjects who perform supervised physical exercise with the methodology used.